Analisis Dampak Keterlambatan Penyampaian Laporan Pertanggungjawaban pada Penyajian Laporan Keuangan Kantor Pelayanan Perbendaharaan Negara (KPPN) Surabaya II (Jurnal Kendali Akuntansi, 2025)
This research aims to analyze the impact of delays in the submission of accountability reports on the presentation of financial statements at KPPN Surabaya II and to examine the legal mechanisms related to the timeliness of LPJ submissions at KPPN Surabaya II. This study employs a qualitative case study approach. Primary data sources were obtained from structured interviews with 2 informants. Secondary data were obtained from documentation, where the required documents were the financial statements of KPPN Surabaya II for the 2023 period, LPJ satker, and letters or reports of administrative sanctions. The informants in this study were selected using purposive sampling with specific criteria, namely individuals who are experienced and directly responsible for the processes of verification, accounting, and financial report preparation. The analysis method in this study uses thematic analysis. The results of this study indicate that most work units have submitted their financial reports on time, but there are still several units that are late. The delays were caused by technical constraints such as disruptions in the SAKTI system and recording errors, as well as human resource factors, particularly related to the adaptation to digital technology. The impact of the delay is the decline in the quality of financial reports due to incorrect entries or inaccurate data from the delayed LPJ, as well as the hindrance of the evaluation and budget allocation processes.